Forward Vol.1(1) - Shrestha, Rajesh (Journal of Foreign Affairs, 2021)
The Institute of Foreign Affairs (IFA) is pleased to bring out The Journal of Foreign Affairs as its key think tank activity. The IFA family was engaged in activities relevant for the publication to materialize the desired outcome. The effort put in so far was successful in laying down the foundation by providing an impetus to future activities to facilitate continued publication of the journal. However, in the course of the publication work, we felt the deficit in necessary human and financial resources. IFA realises the need for reliable network of researchers, experts and academics in contributing to the publication. As it is known to all, health risk and a barrier to movement imposed by the outbreak of COVID-19 had its telling effect on the publication. Despite the obstacles and challenges faced, the outcome, we feel will help academics and stakeholders institutions and enhance the purpose of IFA. The primary and foremost duty of the Institute is to assist the Ministry of Foreign Affairs of Nepal in its discharge of effectively conducting foreign policy practices and understanding. Finally, the Institute extends its deep gratitude to Honourable Foreign Minister Mr Pradeep Kumar Gyawali and the authorities within the Ministry of Foreign Affairs (MoFA) of Nepal for their inspiring support and enabling assistance offered.